Effect of Methanol–NaOH Catalyst Variations on the Properties and Engine Performance of B50 Biodiesel from Waste Cooking Oil - Suardi Suardi; Hariyono Hariyono; Faisal Mahmuddin; M. Rusydi Alwi; Muhammad Uswah Pawara; Alamsyah Alamsyah; Wira Setiawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
The growing demand for environmentally friendly fuels has encouraged the use of biodiesel as an alternative to fossil diesel. This study explores the production of B50 biodiesel derived from waste cooking oil using the transesterification method, with two catalyst variations: (1) 1000 mL methanol + 25 g NaOH and (2) 1200 mL methanol + 30 g NaOH per 5 liters of feedstock. The research aimed to evaluate the effects of catalyst concentration on the physical properties of biodiesel (density, viscosity, and calorific value), as well as its impact on engine performance metrics, including torque, specific fuel consumption (SFC), thermal efficiency, and exhaust gas opacity. Experimental testing was conducted using a four-stroke diesel engine at varying loads and speeds. Results showed that both fuel blends met the Indonesian standards for density, while only the 1200 mL + 30 g NaOH blend met the standard for viscosity. The biodiesel prepared using 1000 mL methanol and 25 g NaOH demonstrated superior engine performance, with a maximum torque of 8.92 Nm, minimum SFC (406.90 g/kWh), and highest thermal efficiency (21.28%) at 1000 RPM and 4000 W load. Additionally, the biodiesel prepared using 1200 mL methanol and 30 g NaOH produced lower exhaust opacity. In conclusion, while increased catalyst dosage improves fuel cleanliness and compliance with standards, the lower catalyst yields the best balance of performance metrics, making it a promising for biodiesel application in diesel engines.